Method for recasting perfluorosulfonic acid membranes at atmospheric pressure and uses thereof

CN118099461BActive Publication Date: 2026-10-27DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211501225.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2026-10-27
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

目前电池中常用的商业化全氟磺酸膜价格昂贵,严重限制着电池技术的商业化和产业化

Benefits of technology

[0043]1)本申请所提供的重铸方法,采用极性材料对废弃全氟磺酸膜进行溶解,降低了全氟磺酸膜的制备温度和压力,实现了全氟磺酸膜的循环再利用,降低了生产成本,提高了工艺安全性,且所制备的膜材料具有高传达率和高稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0003967761360000021
    Figure BDA0003967761360000021
  • Figure BDA0003967761360000022
    Figure BDA0003967761360000022
Patent Text Reader

Abstract

The application discloses a method and application of recasting perfluorosulfonic acid membrane under normal pressure. The recasting method comprises the following steps: a) dissolving raw material containing waste perfluorosulfonic acid membrane in an organic solvent, stirring, and obtaining a perfluorosulfonic acid solution; b) transferring the perfluorosulfonic acid solution to a substrate, and evaporating to obtain a recast perfluorosulfonic acid membrane; the relative polarity test value of the polar solvent ranges from -1 to 0, and the interaction parameter χ of the organic solvent and the perfluorosulfonic acid membrane is located between 1 and 2. The application successfully realizes the dissolution and recasting of the perfluorosulfonic acid membrane under normal pressure by optimizing the solvent. The recast perfluorosulfonic acid membrane has high ion conductivity. The method does not require high temperature and pressurized operation, is simpler and safer, simplifies the production process, reduces the cost, and is suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a method and application for recasting perfluorosulfonic acid membranes under normal pressure, belonging to the field of battery technology. Background Technology

[0002] The consumption of non-renewable fossil fuels and severe environmental pollution have spurred the application of renewable energy sources. However, most renewable energy sources, such as solar and wind power, suffer from uncontrollability, discontinuity, and instability. Electrochemical energy storage technology (i.e., battery technology) can store electrical energy in the form of chemical energy and release it as electrical energy according to user demand, thus addressing the problems inherent in renewable energy applications. Battery technologies, such as lithium-ion batteries, fuel cells, and flow batteries, can undergo repeated reversible charge-discharge processes, making them economical and environmentally friendly. Research on battery technology can promote the widespread application of portable mobile electronic devices and electric vehicles and is crucial for the development of large-scale energy storage technologies. However, the development of electrochemical energy storage technology still faces some serious challenges, such as the safety issues of lithium-ion batteries and the low energy density of flow batteries. Therefore, improving the performance of battery energy storage systems is essential. And improving the performance of battery energy storage systems depends on the development of their key materials.

[0003] The separator is one of the key materials in a secondary battery. It isolates the positive and negative electrodes to prevent short circuits and conducts charge carriers to form a complete circuit. The quality of the separator often determines the performance of the secondary battery. Currently, the commercially available perfluorosulfonic acid (PFSA) membranes commonly used in batteries are expensive, severely limiting the commercialization and industrialization of battery technology. Although PFSA membranes can be recycled, their dissolution is usually carried out under high temperature and pressure, especially in high-pressure reactors, which increases the cost of recasting the PFSA membrane and reduces its safety. Summary of the Invention

[0004] This application proposes a method for dissolving perfluorosulfonic acid membranes under normal pressure, which is based on the polarity of organic solvents to select suitable solvents, further simplifying the production process and reducing costs.

[0005] According to one aspect of this application, a method for recasting a perfluorosulfonic acid membrane under normal pressure is provided, comprising the following steps:

[0006] a) Dissolve the raw material containing the waste perfluorosulfonic acid membrane in an organic solvent and stir to obtain a perfluorosulfonic acid solution;

[0007] b) Transfer the perfluorosulfonic acid solution onto the substrate, evaporate to dryness, and obtain a recast perfluorosulfonic acid membrane;

[0008] The organic solvent is selected from at least two of methanol, ethanol, isopropanol, n-butanol, methanol, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and dimethyl sulfoxide.

[0009] The relative polarity test value of the polar solvent is in the range of -1 to 0, and the interaction parameter χ between the organic solvent and the perfluorosulfonic acid membrane is between 1 and 2.

[0010] It should be noted that the screening of the organic solvents includes the following steps: (1) Obtain the boiling point of a single solvent by consulting the literature. Solvents with boiling points in the range of 50-200℃ can be used to form a mixed solvent.

[0011] (2) Obtain the RPM (relative polarity measure) value of a single solvent by consulting the literature. Solvents with an RPM value range of -1 ≤ RPM < 0 can be used to form mixed solvents.

[0012] (3) Obtain the Hansen solubility parameters of the perfluorosulfonic acid film and the single solvent:

[0013] The Hansen solubility parameters (δ) of the polymers and solvents were obtained through literature review. For polymers whose solubility parameters could not be obtained from literature review, they were calculated using Equation I. For solvents whose solubility parameters could not be obtained from literature review, they were calculated using Equation II.

[0014]

[0015] F i This is the contribution of primary groups to δ, which appears as n in the polymer. i Next; S j This is the contribution of secondary groups to δ, which appears as m in the polymer. j Next. F i With S j All of these can be obtained through literature review.

[0016]

[0017] δ D δ P and δ H These are the dispersive solubility parameter, the polar solubility parameter, and the hydrogen bond solubility parameter, all of which can be obtained from literature.

[0018] (4) Using the Hansen solubility parameters of the perfluorosulfonic acid film and the single solvent, the interaction parameter (χ) between them is calculated using Equation III:

[0019]

[0020] V m δ is the molar volume of the solvent, R and T are the ideal gas constant and absolute temperature, respectively. δ1 and δ2 are the Hansen solubility parameters of the solvent and polymer, respectively. Solvents with χ values ​​between 1 and 2 for perfluorosulfonic acid films can be used to form mixed solvents.

[0021] (5) Calculate the RPM value of the mixed solvent using Equation IV:

[0022] RPM=∑AiBi IV

[0023] Where Ai is the RPM value of a single solvent, and Bi is the mole fraction of this single solvent.

[0024] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated using equation V:

[0025] χ=∑Biχi V

[0026] Where χi is the interaction parameter between the single solvent and the perfluorosulfonic acid film, and Bi is the mole fraction of the single solvent.

[0027] Mixed organic solvents with RPM values ​​between -1 and RPM < 0 and simultaneously with the χ of the perfluorosulfonic acid membrane being between 1 and 2 can be used to dissolve perfluorosulfonic acid membranes under normal pressure.

[0028] The RPM value of the solvent was obtained by consulting the literature (C. Reichardt, Empirical Parameters of Solvent Polarity as Linear Free-Energy Relationships, Angewandte Chemie International Edition, 18(1979)98-110).

[0029] Optionally, the stirring temperature in step (1) is 10-60°C higher than the boiling point of the low-boiling solvent in the selected mixed solvent.

[0030] Optionally, the perfluorosulfonic acid solution contains 2-40% perfluorosulfonic acid by mass.

[0031] Optionally, the stirring temperature is 20–200°C, and the stirring time is 6–120 h.

[0032] Optionally, the stirring temperature is selected from any value or a range between two values ​​from 20°C, 50°C, 100°C, 125°C, 150°C, and 200°C.

[0033] Optionally, the stirring time is selected from any value or a range between two values ​​from 6h, 24h, 48h, 72h, 100h, and 120h.

[0034] Optionally, the evaporation temperature is 20–200°C, and the evaporation time is 1–48 hours.

[0035] Optionally, the evaporation temperature is selected from any value or a range between two values ​​from 20°C, 50°C, 100°C, 125°C, 150°C, and 200°C.

[0036] Optionally, the evaporation time is selected from any value of 1h, 12h, 24h, 36h, 48h or a range between two values.

[0037] Optionally, the substrate is selected from nonwoven fabric or glass plate.

[0038] Optionally, the thickness of the recast perfluorosulfonic acid film is 5–200 μm.

[0039] Optionally, the raw material may also include a perfluorosulfonic acid resin.

[0040] The perfluorosulfonic acid solution prepared in this application can also be blended, compounded, and filled with other membrane materials.

[0041] According to another aspect of this application, the application of a recast perfluorosulfonic acid membrane prepared by any of the above methods in a battery, said battery including a fuel cell or a flow battery, is provided.

[0042] The beneficial effects that this application can produce include:

[0043] 1) The recasting method provided in this application uses polar materials to dissolve waste perfluorosulfonic acid membranes, which reduces the preparation temperature and pressure of perfluorosulfonic acid membranes, realizes the recycling of perfluorosulfonic acid membranes, reduces production costs, improves process safety, and the prepared membrane material has high conductivity and high stability.

[0044] 2) The recasting method provided in this application has a simple and controllable film-making process, which is suitable for large-scale production. Attached Figure Description

[0045] Figure 1 This is a performance comparison of an all-vanadium redox flow battery assembled with a recast PFSA membrane and a commercially available Nafion 115 membrane, as described in Example 1 of this application.

[0046] Figure 2 Cycle performance of the all-vanadium redox flow battery assembled with a recast PFSA membrane according to Example 1 of this application. Detailed Implementation

[0047] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0048] The recast perfluorosulfonic acid membrane prepared using this application can be applied to fuel cells, flow batteries and other fields.

[0049] Example 1

[0050] Traditional solvents such as methanol (MeOH), ethanol (EtOH), isopropanol (IPA), acetone (AC), n-hexane (Hex), water, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and ethyl acetate (EA) were selected to form a mixed solvent. The selection process for the mixed solvent is as follows:

[0051] (I) Relevant parameters of the polymer and solvent were obtained through literature review or formula calculation, including solvent boiling point, RPM value, Hansen solubility parameter, molar volume, and Hansen solubility parameter of the perfluorosulfonic acid film. The solvent boiling point, RPM value, Hansen solubility parameter, and molar volume were obtained through literature review.

[0052] Consult the literature on boiling points: *Lange's Handbook of Chemistry*

[0053] Check the RPM value literature: C. Reichardt, Empirical Parameters of Solvent Polarity as Linear Free-Energy Relationships, Angewandte Chemie International Edition, 18 (1979) 98-110.

[0054] Consult the literature on Hansen solubility parameters and molar volume: "HANSEN SOLUBILITY PARAMETERS A User's Handbook" or "LANGE'S HANDBOOK OF CHEMISTRY".

[0055] The Hansen solubility parameter of the perfluorosulfonic acid membrane was calculated using an empirical formula, with the calculation process referring to patent (application number 202011349983.1), and its Hansen solubility parameter was 18.22 MPa. 1 / 2 (II) Based on literature review, the boiling points of the solvents are shown in Table 1:

[0056] Table 1 Boiling points of different solvents

[0057]

[0058] As shown in Table 1, the boiling points of MeOH, EtOH, IPA, AC, Hex, Water, DMSO, DMF, and EA are all between 50-200℃, and can be further screened.

[0059] (III) Based on literature review, the RPM values ​​of MeOH, EtOH, IPA, AC, Hex, Water, DMSO, DMF, and EA are shown in Table 2:

[0060] Table 2 RPM values ​​for different solvents

[0061]

[0062] As shown in Table 2, the RPM values ​​of MeOH, EtOH, IPA, AC, DMSO, DMF, and EA are between -1 and RPM < 0, and can be further screened.

[0063] (IV) Based on literature review or formula calculation, the Hansen solubility parameters, molar volumes, and interaction parameters with perfluorosulfonic acid films of MeOH, EtOH, IPA, AC, DMSO, DMF, and EA are shown in Table 3:

[0064] Table 3. Hansen solubility parameters, molar volumes, and interaction parameters with perfluorosulfonic acid films for different solvents.

[0065]

[0066]

[0067] As shown in Table 3, the interaction parameters of EtOH, IPA, DMF and perfluorosulfonic acid membrane are between 1 and 2, and can be used to form a mixed solvent for dissolving waste perfluorosulfonic acid membrane.

[0068] The recycling process for perfluorosulfonic acid membranes is as follows:

[0069] (1) Prepare a mixed solvent using EtOH and IPA with a molar ratio of 2:8.

[0070] The RPM of the mixed solvent is calculated as follows:

[0071] RPM=∑AiBi=(-0.68×0.2)+(-0.573×0.8)=-0.5944

[0072] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0073] χ==∑Aiχi=1.77×0.2+1.21×0.8=1.322

[0074] A mixed solvent with an RPM between -1 and 0, and whose χ² value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0075] (2) Cut the perfluorosulfonic acid membrane into small pieces, and then dissolve the cut perfluorosulfonic acid membrane in the mixed solvent prepared in step (1). Stir at a temperature of 100℃ (the boiling points of EtOH and IPA are 78.3℃ and 82.4℃, respectively). It was observed that a uniform perfluorosulfonic acid solution could be prepared after stirring for 8 hours, in which the mass fraction of the perfluorosulfonic acid membrane was 20%.

[0076] (3) Pour the perfluorosulfonic acid solution prepared in step (2) onto the nonwoven fabric substrate, and then evaporate the solvent at 50°C for 4 hours to prepare a recast perfluorosulfonic acid membrane with a thickness of 120 μm, denoted as membrane P1.

[0077] The performance of the P1 membrane was tested and compared with that of the commercially available perfluorosulfonic acid membrane Nafion 115. The sheet resistivity of the P1 membrane was 0.28 Ωcm. 2 The vanadium permeability coefficient is 1.25*10^ -8 cm 2 / min, compared to the sheet resistance of the Nafion 115 film with excellent conductivity (0.29Ωcm). 2 ) and vanadium permeability coefficient (1.24*10^ -8 cm 2 The P1 membrane exhibits similar conductivity ( / min), indicating that the recast P1 membrane possesses high ion conductivity and high ion selectivity (Table 4).

[0078] A vanadium redox flow battery was assembled using the recast P1 membrane, with an activated carbon felt catalyst layer, graphite plates as bipolar plates, and an effective membrane area of ​​48 cm². 2 The current density is 80 mA cm⁻¹ -2 The vanadium ion concentration in the electrolyte is 1.50 mol / L. -1 The concentration of H2SO4 is 3 mol L. -1 The P1 membrane-assembled vanadium redox flow battery exhibits a coulombic efficiency of 94.89%, a voltage efficiency of 87.63%, and an energy efficiency of 83.15%. Figure 1 As shown in Table 5, the efficiencies of the vanadium redox flow batteries assembled with the P1 film and the Nafion 115 film are similar (coulombic efficiency 94.51%, voltage efficiency 87.88%, and energy efficiency 83.06%). Over 100 cycles, the capacity retention of the vanadium redox flow battery assembled with the P1 film is 77%, which is also similar to the capacity retention of the vanadium redox flow battery assembled with the Nafion 115 film (78%) (Table 5). Figure 2As shown, the vanadium redox flow battery assembled with the P1 membrane can operate stably for more than 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0079] Example 2

[0080] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the stirring temperature in step (2) was 110°C, and the recast PFSA membrane was denoted as membrane P2.

[0081] Observations revealed that a homogeneous PFSA solution could be obtained by stirring for 6 hours, indicating that increasing the temperature can accelerate the dissolution of waste perfluorosulfonic acid membranes (Tables 4 and 6).

[0082] The P2 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P2 membrane was 0.27 Ωcm. 2 The vanadium permeability coefficient is 1.26*10^ -8 cm 2 The sheet resistance and vanadium permeability coefficient of the recast P2 membrane are similar to those of the Nafion 115 membrane, which has excellent conductivity, indicating that the recast P2 membrane has high ion conductivity and high ion selectivity (Table 4).

[0083] The vanadium redox flow battery assembled using the P2 membrane achieved a coulombic efficiency of 94.92%, a voltage efficiency of 87.65%, and an energy efficiency of 83.20%. After 100 cycles, its capacity retention was 78%, similar to that of the vanadium redox flow battery assembled using the Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P2 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0084] Example 3

[0085] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the molar ratio of EtOH to IPA in step (1) was 8:2, and the recast PFSA membrane was denoted as membrane P3.

[0086] The RPM of the mixed solvent is calculated as follows:

[0087] RPM=∑AiBi=(-0.68×0.8)+(-0.573×0.2)=-0.6586

[0088] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0089] χ=∑Aiχi=1.77×0.8+1.21×0.2=1.658

[0090] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0091] Observations revealed that a homogeneous PFSA solution could be obtained after stirring for 9 hours (Table 4). This is because the amount of IPA, which has a lower interaction parameter with the perfluorosulfonic acid membrane, was reduced, which increased the interaction parameter between the mixed solvent and the perfluorosulfonic acid membrane, weakened the interaction between the mixed solvent and the perfluorosulfonic acid membrane, and worsened the solubility of the perfluorosulfonic acid membrane (Table 6).

[0092] The P3 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P3 membrane was 0.28 Ωcm. 2 The vanadium permeability coefficient is 1.23*10^ -8 cm 2 / min, compared with the sheet resistance and vanadium permeability coefficient of the Nafion 115 membrane, which has excellent conductivity (1.24*10^ -8 Similarly, this indicates that the recast P3 membrane has high ion conductivity and high ion selectivity (Table 4).

[0093] A vanadium redox flow battery was assembled using a P3 membrane. Its coulombic efficiency was 94.95%, voltage efficiency was 87.61%, and energy efficiency was 83.19%. After 100 cycles, the capacity retention was 79%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P3 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0094] Example 4

[0095] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) consisted of EtOH and DMF in a molar ratio of 8:2, and the recast PFSA membrane was denoted as membrane P4.

[0096] The RPM of the mixed solvent is calculated as follows:

[0097] RPM=∑AiBi=(-0.68×0.8)+(-0.471×0.2)=-0.6382

[0098] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0099] χ=∑Aiχi=1.77×0.8+1.71×0.2=1.758

[0100] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0101] Observations revealed that a homogeneous PFSA solution could be obtained by stirring for 10 hours (Table 4). This is because the interaction parameters between the mixed solvent and the perfluorosulfonic acid membrane increased, while the interaction between the mixed solvent and the perfluorosulfonic acid membrane weakened, resulting in poorer solubility of the perfluorosulfonic acid membrane (Table 6).

[0102] The P4 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P4 membrane was 0.29 Ωcm. 2 The vanadium permeability coefficient is 1.22*10^ -8 cm 2 The sheet resistance and vanadium permeability coefficient of the recast P4 membrane are similar to those of the Nafion 115 membrane, which has excellent conductivity, indicating that the recast P4 membrane has high ion conductivity and high ion selectivity (Table 4).

[0103] A vanadium redox flow battery was assembled using a P4 membrane. Its coulombic efficiency was 94.98%, voltage efficiency was 87.59%, and energy efficiency was 83.19%. Within 100 cycles, the capacity retention was 80%, similar to the efficiency and capacity retention of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P4 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0104] Example 5

[0105] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the solvent used in step (1) was a mixed solvent of EtOH and DMF, with a molar ratio of EtOH to DMF of 2:8. The recast PFSA membrane was denoted as membrane P5.

[0106] The RPM of the mixed solvent is calculated as follows:

[0107] RPM=∑AiBi=(-0.68×0.2)+(-0.471×0.8)=-0.5128

[0108] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0109] χ=∑Aiχi=1.77×0.2+1.71×0.8=1.722

[0110] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0111] Observations revealed that a homogeneous PFSA solution could be obtained by stirring for 9.5 hours (Table 4). This is because, compared to Example 4, the interaction parameters between the mixed solvent and the perfluorosulfonic acid membrane decreased, which improved the interaction between the mixed solvent and the perfluorosulfonic acid membrane, making the perfluorosulfonic acid membrane easier to dissolve (Table 6).

[0112] The P5 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P5 membrane was 0.28 Ωcm. 2 The vanadium permeability coefficient is 1.22*10^ -8 cm 2 The P5 membrane has a surface resistivity and vanadium permeability coefficient similar to those of the Nafion 115 membrane with excellent conductivity, indicating that the recast P5 membrane has high ion conductivity and high ion selectivity (Table 4).

[0113] A vanadium redox flow battery was assembled using a P5 membrane. Its coulombic efficiency was 94.99%, voltage efficiency was 87.61%, and energy efficiency was 83.22%. After 100 cycles, the capacity retention was 80%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P5 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0114] Example 6

[0115] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) consisted of IPA and DMF with a molar ratio of 2:8. The recast PFSA membrane was denoted as membrane P6.

[0116] The RPM of the mixed solvent is calculated as follows:

[0117] RPM=∑AiBi=(-0.573×0.2)+(-0.471×0.8)=-0.4914

[0118] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0119] χ=∑Aiχi=1.21×0.2+1.71×0.8=1.61

[0120] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0121] Observations revealed that a homogeneous PFSA solution could be obtained by stirring for 8.5 hours (Table 4). This is because, compared to Example 4, replacing EtOH with IPA, which has a lower interaction parameter with the perfluorosulfonic acid membrane, reduced the interaction parameter between the mixed solvent and the perfluorosulfonic acid membrane, thereby increasing the interaction between the mixed solvent and the perfluorosulfonic acid membrane and making the perfluorosulfonic acid membrane easier to dissolve.

[0122] The P6 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P6 membrane was 0.28 Ωcm. 2 The vanadium permeability coefficient is 1.24*10^ -8 cm 2 The sheet resistance and vanadium permeability coefficient of the recast P6 membrane are similar to those of the Nafion 115 membrane, which has excellent conductivity, indicating that the recast P6 membrane has high ion conductivity and high ion selectivity (Table 4).

[0123] A vanadium redox flow battery was assembled using a P6 membrane. Its coulombic efficiency was 94.97%, voltage efficiency was 87.60%, and energy efficiency was 83.19%. After 100 cycles, the capacity retention was 79%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P6 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0124] Example 7

[0125] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) consisted of IPA and DMF, and the molar ratio of EtOH to DMF was 8:2. The recast PFSA membrane was denoted as membrane P7.

[0126] The RPM of the mixed solvent is calculated as follows:

[0127] RPM=∑AiBi=(-0.573×0.8)+(-0.471×0.2)=-0.5526

[0128] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0129] χ=∑Aiχi=1.21×0.8+1.71×0.2=1.31

[0130] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0131] Observations revealed that a homogeneous PFSA solution could be obtained after stirring for 7 hours (Table 4). This is because, compared to Example 6, the IPA content, which has a lower interaction parameter with the perfluorosulfonic acid membrane, increased, significantly reducing the interaction parameter between the mixed solvent and the perfluorosulfonic acid membrane. The interaction between the mixed solvent and the perfluorosulfonic acid membrane was significantly enhanced, resulting in a marked improvement in the solubility of the perfluorosulfonic acid membrane.

[0132] The P7 membrane was subjected to performance testing and compared with the performance of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P7 membrane was 0.27 Ωcm. 2 The vanadium permeability coefficient is 1.23*10^ -8 cm 2 The sheet resistance and vanadium permeability coefficient of the recast P7 membrane are similar to those of the Nafion 115 membrane, which has excellent conductivity, indicating that the recast P7 membrane has high ion conductivity and high ion selectivity (Table 4).

[0133] A vanadium redox flow battery was assembled using a P7 membrane. Its coulombic efficiency was 94.96%, voltage efficiency was 87.64%, and energy efficiency was 83.22%. After 100 cycles, the capacity retention was 79%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P7 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0134] Example 8

[0135] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) consisted of EtOH, IPA and DMF in a molar ratio of 2:4:4, and the recast PFSA membrane was denoted as membrane P8.

[0136] The RPM of the mixed solvent is calculated as follows:

[0137] RPM=∑AiBi=(-0.68×0.2)+(-0.573×0.4)+(-0.471×0.4)=-0.5536

[0138] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0139] χ=∑Aiχi=1.77×0.2+1.21×0.4+1.71×0.4=1.522

[0140] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0141] Observations revealed that a homogeneous PFSA solution could be obtained after stirring for 8.2 hours (Table 4). This is because, compared to Example 1, the decrease in IPA content (which has a lower interaction parameter with the perfluorosulfonic acid membrane) and the addition of DMF (which has a higher interaction parameter with the perfluorosulfonic acid membrane) increased the interaction parameter between the mixed solvent and the perfluorosulfonic acid membrane. Consequently, the interaction between the mixed solvent and the perfluorosulfonic acid membrane weakened, resulting in a significant decrease in the solubility of the perfluorosulfonic acid membrane (Table 6).

[0142] The P8 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P8 membrane was 0.26 Ωcm. 2 The vanadium permeability coefficient is 1.21*10^ -8 cm 2 The sheet resistance and vanadium permeability coefficient of the recast P8 membrane are similar to those of the Nafion 115 membrane, which has excellent conductivity, indicating that the recast P8 membrane has high ion conductivity and high ion selectivity (Table 4).

[0143] A vanadium redox flow battery was assembled using a P8 membrane. Its coulombic efficiency was 95.01%, voltage efficiency was 87.69%, and energy efficiency was 83.31%. After 100 cycles, the capacity retention was 79%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P8 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0144] Example 9

[0145] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) consisted of EtOH, IPA and DMF in a molar ratio of 4:2:4, and the recast PFSA membrane was denoted as membrane P9.

[0146] The RPM of the mixed solvent is calculated as follows:

[0147] RPM=∑AiBi=(-0.68×0.4)+(-0.573×0.2)+(-0.471×0.4)=-0.575

[0148] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0149] χ=∑Aiχi=1.77×0.4+1.21×0.2+1.71×0.4=1.634

[0150] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0151] Observations revealed that a homogeneous PFSA solution could be obtained after stirring for 8.7 hours (Table 4). This is because, compared to Example 8, the decrease in IPA content (which has a lower interaction parameter with the perfluorosulfonic acid membrane) and the increase in EtOH content (which has a higher interaction parameter with the perfluorosulfonic acid membrane) led to an increase in the interaction parameter between the mixed solvent and the perfluorosulfonic acid membrane. Consequently, the interaction between the mixed solvent and the perfluorosulfonic acid membrane weakened, resulting in a significant decrease in the solubility of the perfluorosulfonic acid membrane and a prolonged dissolution time.

[0152] The P9 membrane was subjected to performance testing and its performance was compared with that of the commercially available perfluorosulfonic acid membrane, Nafion 115. The sheet resistivity of the P9 membrane was 0.30 Ωcm. 2 The vanadium permeability coefficient is 1.22*10^ -8 cm 2 The P9 membrane has a permeability of / min, similar to that of the Nafion 115 membrane with excellent conductivity (sheet resistance and vanadium permeability coefficient), indicating that the recast P9 membrane has high ion conductivity and high ion selectivity (Table 4).

[0153] A vanadium redox flow battery was assembled using a P9 membrane. Its coulombic efficiency was 94.98%, voltage efficiency was 87.62%, and energy efficiency was 83.22%. After 100 cycles, the capacity retention was 79%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P9 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0154] Example 10

[0155] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) consisted of EtOH, IPA and DMF in a molar ratio of 4:4:2, and the recast PFSA membrane was denoted as membrane P10.

[0156] The RPM of the mixed solvent is calculated as follows:

[0157] RPM=∑AiBi=(-0.68×0.4)+(-0.573×0.4)+(-0.471×0.2)=-0.5954

[0158] The interaction parameters between the mixed solvent and the perfluorosulfonic acid film were calculated as follows:

[0159] χ=∑Aiχi=1.77×0.4+1.21×0.4+1.71×0.2=1.534

[0160] A mixed solvent with an RPM between -1 and RPM < 0, and whose χ value is between 1 and 2, can be used to dissolve perfluorosulfonic acid membranes.

[0161] Observations revealed that a homogeneous PFSA solution could be obtained after stirring for 8.3 hours (Table 4). This is because, compared to Example 9, the increased content of IPA (which has a lower interaction parameter with the perfluorosulfonic acid membrane) and the decreased content of DMF (which has a higher interaction parameter with the perfluorosulfonic acid membrane) lowered the interaction parameter between the mixed solvent and the perfluorosulfonic acid membrane, thus enhancing the interaction between the mixed solvent and the perfluorosulfonic acid membrane. This improved the solubility of the perfluorosulfonic acid membrane and shortened the dissolution time.

[0162] The performance of the P10 membrane was tested and compared with that of the commercially available perfluorosulfonic acid membrane Nafion 115. The sheet resistivity of the P10 membrane was 0.29 Ωcm. 2 The vanadium permeability coefficient is 1.25*10^ -8 cm 2 The sheet resistivity and vanadium permeability coefficient of the recast P10 membrane are similar to those of the Nafion 115 membrane, which has excellent conductivity, indicating that the recast P10 membrane has high ion conductivity and high ion selectivity (Table 4).

[0163] A vanadium redox flow battery was assembled using a P10 membrane. Its coulombic efficiency was 94.94%, voltage efficiency was 87.66%, and energy efficiency was 83.22%. After 100 cycles, the capacity retention was 78%, similar to that of a vanadium redox flow battery assembled using a Nafion 115 membrane (Table 5). Furthermore, the vanadium redox flow battery assembled using the P10 membrane could operate stably for over 2000 cycles without significant performance degradation, demonstrating excellent stability.

[0164] Comparative Example 1

[0165] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the solvent used in step (1) was a single solvent EtOH. It was observed that the perfluorosulfonic acid membrane still did not dissolve after stirring for 72 hours. This is because a single solvent with RPM between -1 and RPM < 0 and with the χ of the perfluorosulfonic acid membrane between 1 and 2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0166] Comparative Example 2

[0167] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the solvent used in step (1) was a single solvent IPA. It was observed that the perfluorosulfonic acid membrane still did not dissolve after stirring for 72 hours. This is because a single solvent with RPM between -1 and RPM < 0 and with the χ of the perfluorosulfonic acid membrane between 1 and 2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0168] Comparative Example 3

[0169] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the solvent used in step (1) was a single solvent DMF. It was observed that the perfluorosulfonic acid membrane still did not dissolve after stirring for 72 hours. This is because a single solvent with RPM between -1 and RPM < 0 and with the χ of the perfluorosulfonic acid membrane between 1 and 2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0170] Comparative Example 4

[0171] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH and Hex (RPM = 0). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM not in the range of -1 ≤ RPM < 0 and a single solvent with RPM in the range of -1 ≤ RPM < 0 and simultaneously with the perfluorosulfonic acid membrane with x in the range of 1-2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0172] Comparative Example 5

[0173] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH and Water (RPM = -1.042). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM not in the range of -1 ≤ RPM < 0 and a single solvent with RPM in the range of -1 ≤ RPM < 0 and simultaneously with the perfluorosulfonic acid membrane with χ between 1 and 2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0174] Comparative Example 6

[0175] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH and MeOH (interaction parameter with perfluorosulfonic acid membrane = 2.47). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x-value with the perfluorosulfonic acid membrane is not in the range of 1-2, and a single solvent with RPM in the range of -1 ≤ RPM < 0 and whose x-value with the perfluorosulfonic acid membrane is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0176] Comparative Example 7

[0177] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH and AC (interaction parameter with perfluorosulfonic acid membrane = 0.46). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x-value with the perfluorosulfonic acid membrane is not in the range of 1-2, and a single solvent with RPM in the range of -1 ≤ RPM < 0 and whose x-value with the perfluorosulfonic acid membrane is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0178] Comparative Example 8

[0179] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH and DMSO (interaction parameter with the perfluorosulfonic acid membrane = 2.41). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x-value with the perfluorosulfonic acid membrane is not in the range of 1-2, and a single solvent with RPM in the range of -1 ≤ RPM < 0 and whose x-value with the perfluorosulfonic acid membrane is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0180] Comparative Example 9

[0181] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH and EA (interaction parameter with the perfluorosulfonic acid membrane = 0.34). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x-value with the perfluorosulfonic acid membrane is not in the range of 1-2, and a single solvent with RPM in the range of -1 ≤ RPM < 0 and whose x-value with the perfluorosulfonic acid membrane is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0182] Comparative Example 10

[0183] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the stirring temperature in step (1) was 80°C. It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours. This was because the temperature was too low, which reduced the solubility of the perfluorosulfonic acid membrane.

[0184] Comparative Example 11

[0185] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the stirring temperature in step (1) was 150°C. It was observed that the perfluorosulfonic acid membrane dissolved after stirring for 6 hours. However, the stirring temperature was too high, the energy consumption was too high, and it was not conducive to large-scale production.

[0186] Comparative Example 12

[0187] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was IPA and AC (interaction parameter with perfluorosulfonic acid membrane = 0.46). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x-value with the perfluorosulfonic acid membrane is not in the range of 1-2, and a single solvent with RPM in the range of -1 ≤ RPM < 0 and whose x-value with the perfluorosulfonic acid membrane is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0188] Comparative Example 13

[0189] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was DMF and AC (interaction parameter with perfluorosulfonic acid membrane = 0.46). It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the mixed solvent composed of a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x-value with the perfluorosulfonic acid membrane is not in the range of 1-2, and a single solvent with RPM in the range of -1 ≤ RPM < 0 and whose x-value with the perfluorosulfonic acid membrane is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0190] Comparative Example 14

[0191] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH, IPA and Hex. It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the new mixed solvent composed of a single solvent with RPM not in the range of -1≤RPM<0 and multiple single solvents with RPM in the range of -1≤RPM<0 and whose x value of the perfluorosulfonic acid membrane is between 1 and 2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0192] Comparative Example 15

[0193] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH, IPA, DMF and Hex. It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because the new mixed solvent composed of a single solvent with RPM not in the range of -1≤RPM<0 and multiple single solvents with RPM in the range of -1≤RPM<0 and whose x value of the perfluorosulfonic acid membrane is between 1 and 2 cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0194] Comparative Example 16

[0195] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH, IPA and DMSO. It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x value is not in the range of 1-2, and multiple single solvents with RPM in the range of -1 ≤ RPM < 0 and whose x value is in the range of 1-2, together with the new mixed solvent composed of multiple single solvents with RPM in the range of -1 ≤ RPM < 0 and whose x value is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0196] Comparative Example 17

[0197] The PFSA membrane was recast according to the method (process and conditions) described in Example 1, except that the mixed solvent used in step (1) was EtOH, IPA, DMF and DMSO. It was observed that the perfluorosulfonic acid membrane did not dissolve after stirring for 72 hours, regardless of the molar ratio. This is because a single solvent with RPM in the range of -1 ≤ RPM < 0 but whose x value is not in the range of 1-2, and multiple single solvents with RPM in the range of -1 ≤ RPM < 0 and whose x value is in the range of 1-2, together with the new mixed solvent composed of multiple single solvents with RPM in the range of -1 ≤ RPM < 0 and whose x value is in the range of 1-2, cannot dissolve the waste perfluorosulfonic acid membrane (Tables 4 and 6).

[0198] Table 4. Composition of the mixed solvents and physicochemical properties of the recast PFSA films in the examples and comparative examples.

[0199]

[0200]

[0201] Table 5 shows the performance of the all-vanadium redox flow batteries assembled with the recast PFST membrane.

[0202] Nafion 115 64.51 87.88 83.06 78 P1 EtOH:IPA=2:8 94.89 87.63 83.15 77 P2 EtOH:IPA=2:8 94.92 87.65 83.20 78 P3 EtOH:IPA=8:2 94.95 87.61 83.19 79 P4 EtOH:DMF=8:2 94.98 87.59 83.19 80 P5 EtOH:DMF=2:8 94.99 87.61 83.22 80 P6 IPA:DMF=2:8 94.97 87.60 83.19 79 P7 IPA:DMF=8:2 94.96 87.64 83.22 79 P8 EtOH:IPA:DMF=2:4:4 95.01 87.69 83.31 79 P9 EtOH:IPA:DMF=4:2:4 94.98 87.62 83.22 79 P10 EtOH:IPA:DMF=4:4:2 94.94 87.66 83.22 78

[0203] Table 6 Explanation of the phenomena in the examples and comparative examples

[0204]

[0205]

[0206] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for recasting a perfluorosulfonic acid membrane under normal pressure, characterized in that, Includes the following steps: a) Dissolve the raw material containing waste perfluorosulfonic acid membrane in a mixed organic solvent and stir to obtain a perfluorosulfonic acid solution; the stirring temperature is 100~200℃; b) Transfer the perfluorosulfonic acid solution onto the substrate, evaporate to dryness, and obtain a recast perfluorosulfonic acid membrane; The mixed organic solvent is selected from at least two of ethanol, isopropanol, and N,N-dimethylformamide; The relative polarity test value (RPM) of the mixed organic solvent is in the range of -1 ≤ RPM < 0, and the interaction parameters between the mixed organic solvent and the perfluorosulfonic acid membrane are... χ Located between 1 and 2; The screening of the mixed organic solvents includes the following steps: (1) Obtain the boiling point of a single solvent by consulting the literature, and select solvents with boiling points between 50-200°C. o Further screening will be conducted using single solvents within the range of C; (2) Obtain the relative polarity test value (RPM) of a single solvent by consulting the literature, and further screen single solvents with an RPM value range of -1≤RPM<0. (3) Obtain the Hansen solubility parameters of the perfluorosulfonic acid membrane and the single solvent; (4) The interaction parameters between the perfluorosulfonic acid film and the single solvent are calculated using Equation III based on the Hansen solubility parameters of the perfluorosulfonic acid film and the single solvent. χ : ...... III V m Where R is the molar volume of a single solvent, and T is the ideal gas constant and absolute temperature, respectively. δ 1 and δ 2. Hansen solubility parameters of the polymer in a single solvent and a perfluorosulfonic acid film, respectively; and interaction parameters with the perfluorosulfonic acid film. χ A single solvent in the range of 1-2 is used to form a mixed organic solvent; (5) Calculate the RPM value of the mixed organic solvent using Equation IV: ......IV Where Ai is the RPM value of a single solvent, and Bi is the mole fraction of this single solvent; The interaction parameters between the mixed organic solvent and the perfluorosulfonic acid film were calculated using equation V: ......V in, The interaction parameter between the single solvent and the perfluorosulfonic acid membrane is represented by Bi, which is the mole fraction of the single solvent. Among them, the interaction parameters of RPM values ​​between -1 and RPM < 0 and the perfluorosulfonic acid membrane are considered. χ Mixed organic solvents in the range of 1-2 are used for the dissolution of waste perfluorosulfonic acid membranes under normal pressure.

2. The method according to claim 1, characterized in that, The perfluorosulfonic acid solution contains 2-40% perfluorosulfonic acid by mass.

3. The method according to claim 1, characterized in that, The stirring time is 6~120h.

4. The method according to claim 1, characterized in that, The evaporation temperature is 20~200℃, and the evaporation time is 1h~48h.

5. The method according to claim 1, characterized in that, The substrate is selected from non-woven fabric or glass plate.

6. The method according to claim 1, characterized in that, The thickness of the recast perfluorosulfonic acid film is 5~200μm.

7. The method according to claim 1, characterized in that, The raw materials also include perfluorosulfonic acid resin.

8. The application of a recast perfluorosulfonic acid membrane prepared by the method according to any one of claims 1 to 7 in a battery, said battery comprising a fuel cell or a flow battery.

Citation Information

Patent Citations

  • A composite membrane, its preparation method, and its application

    CN114551918B

  • Preparation method of perfluorinated sulfonic acid resin solid

    CN113754820A

  • Preparation method of perfluorinated sulfonic acid resin dispersion liquid

    CN114276561A